College Students' Perception of Cardiovascular Disease in Yogyakarta - Lies Permana; Yayi Suryo Prabandari; Ari Natalia Probandari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2022)
Background: Cardiovascular disease has been found in young people because of the unhealthy lifestyle that is lived by many younger people. Packed activities, social life, and students’ assiduity affect their lifestyle. Each student lives a different lifestyle depending on their motivation, therefore it’s necessary to do research in order to investigate students’ lifestyles, consist of smoking behavior, eating behavior, and physical activity, using the Protection Motivation Theory, which consists of perceived vulnerability and severity of cardiovascular disease, response efficacy, and self-efficacy of healthy behavior. This research aimed to ascertain students’ healthy lifestyle as protection against cardiovascular disease. Methods: The research was done using the qualitative method with a phenomenology approach. The data were gathered by doing comprehensive interviews with 14 informants in a purposive way with maximum variation sampling, at four universities in Yogyakarta Province. The research was conducted from May to July 2015. Results: The results indicated that students have yet lived healthily due to some common habits such as smoking, unhealthy diet, lack of exercise, and other discoveries such as coffee and alcohol consumption. The attempt of protection against cardiovascular disease wasn’t habitually done yet by students because of their young age and their customary thought that cardiovascular disease mostly happens to elderly people. Students haven’t been aware yet that they are not resistant to cardiovascular disease. One of the reasons was how insufficient the student’s awareness was when it comes to cardiovascular disease. Their perception of the disease severity was adequate due to the fact that they have seen directly the consequences that were caused by cardiovascular disease. The students’ response efficacy and self-efficacy in doing a healthy lifestyle were also considered low because the access to make a healthy lifestyle was still less. Conclusion: The student's awareness of the cardiovascular disease was still low. Among the four parts of Protection Motivation Theory, the part on severity perception was quite decent due to the fact that they had seen directly the consequences that were caused by cardiovascular disease. Each university needs to provide health care services in order to promote a healthy lifestyle, particularly among students.